Psychometric properties of lift and carry test in assessing people with stroke - Chen, Peiming; Tse, Mimi M. Y; Ng, Shamay S.M.; Ho, Leo C. M.; Kwok, Anthony T. C.; Lam, Sam C. Y.; Liu, Tai Wa; Wong, Thomson W. L.; So, Billy C. L.; Lai, Cynthia Y. Y. (Frontiers in Neurology, 2024)
Objective To investigate the psychometric properties of the Lift and Carry Test (LCT) time in people with stroke. Design Cross-sectional design. Setting University based neurorehabilitation laboratory. Participants Twenty-four people with stroke and 24 healthy controls. Outcome measures Lift and Carry Test (LCT), Fugl-Meyer Assessment of upper extremity and lower extremity, ankle dorsiflexor and plantarflexor muscle strength, Berg Balance Scale (BBS), Timed Up and Go (TUG) and Community Integration Measure. Results The mean LCT time (29.70s) in people with stroke was more than double of that in healthy controls (13.70s). The LCT showed excellent intra-rater, inter-rater and test–retest reliability [intraclass correlation coefficient (ICC) = 0.943–1.000]. The LCT times demonstrated a significant negative correlation with the BBS score (rs = −0.771) and significant positive correlations with the TUG times (rs = 0.933). There was no significant correlation between LCT times and FMA score (p > 0.05). An optimal cut-off LCT time of 15.48 s (sensitivity = 95.8%, specificity = 87.5%) was identified to differentiate between people with stroke and healthy controls (area under the curve = 0.957). Conclusion LCT is an excellent clinical test for examining advanced functional ability in people with stroke and distinguishing people with stroke from healthy controls.